2012
DOI: 10.1089/jop.2011.0070
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomographic Patterns in Diabetic Macula Edema Can Predict the Effects of Intravitreal Bevacizumab Injection as Primary Treatment

Abstract: Patients with CME gained greater improvement in visual acuity and macular thickness and volume after IVB injection had been administered as the primary treatment for DME, as compared with other patients. The OCT patterns of DME may indicate the appropriate treatment; we consider these patterns to be prognostic of the response to IVB injection for macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 30 publications
2
38
1
1
Order By: Relevance
“…Our observations that number and size of ONL cysts decrease over the course of treatment with intravitreally injected Ranibizumab in patients with DME support the positive effect of anti-VEGF treatment seen in previous works on cystoid macular oedema and may indicate an improved inner blood-retina barrier due to the above mentioned anti-VEGF effect on vascular permeability (Wu et al 2012). Over the course of anti-VEGF treatment, the well-known improvement of the macular function was accompanied by a significant regression of ONL cysts with a significant decrease in their size.…”
Section: Discussionsupporting
confidence: 89%
“…Our observations that number and size of ONL cysts decrease over the course of treatment with intravitreally injected Ranibizumab in patients with DME support the positive effect of anti-VEGF treatment seen in previous works on cystoid macular oedema and may indicate an improved inner blood-retina barrier due to the above mentioned anti-VEGF effect on vascular permeability (Wu et al 2012). Over the course of anti-VEGF treatment, the well-known improvement of the macular function was accompanied by a significant regression of ONL cysts with a significant decrease in their size.…”
Section: Discussionsupporting
confidence: 89%
“…However, such patients exhibit a decreased response to anti-VEGF therapy. Previously, VMIAs were found to associate with the use of intravitreal anti-VEGF agents in cases of persistent DME (5,6) . Wu et al suggested that DME with VMIAs may correlate with a poor outcome after anti-VEGF treatment; however, the authors of that study followed patients who received only a single 1.25-mg injection of bevacizumab during a 3-month study period (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, VMIAs were found to associate with the use of intravitreal anti-VEGF agents in cases of persistent DME (5,6) . Wu et al suggested that DME with VMIAs may correlate with a poor outcome after anti-VEGF treatment; however, the authors of that study followed patients who received only a single 1.25-mg injection of bevacizumab during a 3-month study period (5) . Yoon et al studied whether the administration of 3 anti-VEGF injections (either 0.3 mg ranibizumab or 1.25 mg bevacizumab) would affect BCVA and CMT in patients with DME with VMIAs, and observed that significantly reduced improvements in the BCVA of patients with both DME and VMIAs, compared to those with only DME (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect to monotherapy with IVB, some authors [25,26] concluded that visual acuity outcomes are better in DRT than in СМЕ and SRD. Others [27,28] found that IVB gives the best results in СМЕ.…”
Section: Discussionmentioning
confidence: 99%